GEOSCIENCES MUSEUM, UNIVERSITY EXTENSION, AND KNOWLEDGE PRODUCTION: ARTICULATIONS AMONG TEACHING, RESEARCH, AND EDUCATIONAL TRAINING IN GEOGRAPHY, SCIENCE, AND HISTORY EDUCATION - Campos, Ricardo Aparecido; Vieira, Fernando Bessa Gonçalves; de Souza, Vitória Graciliano Batista; Silva, Vitória Antonielli Leal; Ferreira, Karla dos Santos; Leopoldo, Gabrielly Esperanelino; Rosa, Izabelly Aparecida; dos Santos, Rayra (Seven Editora, 2026)
This study aims to analyze the contributions of research and extension projects linked to the Geosciences Museum of the State University of Northern Paraná (UENP), highlighting their articulation with teaching, teacher education, and scientific knowledge production. Methodologically, this is a qualitative study based on bibliographic review, document analysis, and systematization of institutional practices. The research is grounded in theoretical frameworks addressing the social role of the university, critical epistemology, and the role of museums as spaces of scientific mediation, drawing on authors such as Santos, Freire, Hooper-Greenhill, and Cavalcanti. The results indicate that the Geosciences Museum functions as a strategic space for integrating teaching, research, and extension, contributing to the preservation of geological and archaeological heritage, as well as to scientific education and geographical literacy. Furthermore, the study highlights advances in student training through participation in research and extension projects, particularly through the use of active methodologies, innovative teaching resources, and digital technologies. It is concluded that the articulation between university and society strengthens the construction of a more democratic, interdisciplinary, and socially engaged science.